DEVELOPMENT OF AUDIO VISUAL LEARNING MEDIA ANDROID MECHANICAL MEASURING TOOLS FOR IMPROVING LEARNING OUTCOMES AT VOCATIONAL SECONDARY SCHOOL - Iwan, Dartiwan iwan; Permana, Tatang; Sriyono, Sriyono (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
The low value of Competency Unit Test (UUK) and Mid-Semester Exam (UTS) in Basic Work Automotive Engineering (PDTO) basic competency of mechanical measuring instruments, especially using and read the measurement results of the vernier caliper, micrometer and dial indicator at SMKN 8 Bandung. Users Android among students are very many and continue to develop, it is possible that Android technology is used as a learning medium for mechanical measuring instruments. The objectives of this research are (1) To create and develop learning media for basic competency of android-based mechanical measuring instruments, (2) to see the learning achievement of students with the basic competencies of mechanical measuring instruments, and (3) to see the responses of students using android-based applications in learning. This study uses thedevelopment model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The research design used the Pre Experimental Design with the type of One Group Pre Test Post Test. The results of this study indicate an increase in understanding of using and reading the measurement results of mechanical measuring instruments after applying Android-based learning media in the moderate category.